0448 Self-care trajectories and sleep characteristics in people with heart failure and insomnia. (25th May 2022) - Conley, Samantha; Jeon, Sangchoon; OConnell, Meghan; Redeker, Nancy
Abstract: Introduction: Sleep disturbance is common among people with heart failure (HF) and associated with poor self-care. The purpose of this study, a secondary analysis of data from a randomized controlled trial of the sustained effects of cognitive behavioral therapy for insomnia compared to HF self-management, was to examine the extent to which these interventions improved HF self-care trajectories and the associations between changes in sleep and self-care trajectories. Methods: We measured changes in self-care maintenance (daily activities), management (symptom management), and confidence (self-efficacy), components of self-care (SC: Self-care of Heart Failure Index) and self-reported sleep characteristics [Insomnia Severity Index (ISI), Pittsburgh Sleep Quality Index (PSQI), daytime sleepiness (PROMIS Sleep Impairment)] at baseline and 3, 6, and 12 months post-intervention. We used group-based trajectory modeling to identify self-care trajectories and generalized linear models to identify the associations between changes in sleep and SC trajectories. Results: We included 175 participants [N = 91 HS; age M = 63 years (12.9); n = 110 (57.1%) male; n = 133 (76.0%) White]. At baseline, SC maintenance, management, and confidence were poor overall [M = 66.3 (16.4); 53.4 (23.8); 68.1 (20.3), respectively]. We identified four self-care trajectories. Class A (poor SC maintenance & management; moderate confidence: N = 47, 26.9%); Class B (low self-care management & confidence, moderate maintenance: N = 68, 38.9%): Class C (high maintenance & management, low confidence; N = 42, 24.0%); Class D (high on all SC: N = 18, 10.3%). There was no significant difference in changes in self-care over time between HS and HH, but both groups improved at 3 and 6 months on self-care maintenance, and self-care management improved at 12 months over baseline (p < .05). Participants in all classes improved on insomnia severity and sleepiness (p< .05) over time. Conclusion: We found that insomnia and sleepiness improved even those with poor self-care suggesting that adequate HF SC may not be needed to improve insomnia. Future research is needed to determine if a combination of HF self-management and CBT-I improves SC trajectories in this population. Support (If Any): R01NR016191 and P20NR014126